Role of defects and phonons in bandgap dynamics of monolayer WS2 at high carrier densities. (3rd December 2020) - Brasington, Alexandra; Golla, Dheeraj; Dave, Arpit; Chen, Bin; Tongay, Sefaattin; Schaibley, John; LeRoy, Brian J; Sandhu, Arvinder
Abstract: We conduct ultrafast pump-probe spectroscopy in monolayer WS2 at high pump fluences to gain direct insight into interactions between a high density of carriers, defects, and phonons. We find that defects in the lattice play a major role in determining the relaxation dynamics by trapping the photoexcited carriers and acting as non-radiative recombination centers that emit phonons. In the high carrier density regime explored in our experiments, we observe substantial changes in the transient absorbance signal at unexpectedly long-time delays which we attribute to phonon-induced band gap modification. Our probe frequency dependent measurements and modeling indicate a renormalization of the bandgap by up to 23 meV. These results highlight the importance of defects and phonons for optical applications of monolayer transition metal dichalcogenides.